Cyclic behaviour of elliptical-shaped reduced web section connection. (April 2020) - Davarpanah, Mohammad; Ronagh, Hamid; Memarzadeh, Parham; Behnamfar, Farhad
Abstract: In this paper, an RWS connection with an elliptic opening in the web is proposed, and its performance is investigated through an experimental and numerical study. A full-scale elliptical RWS connection was experimentally tested under cyclic loading, to evaluate the performance of the connection and to use for verifying the validity of numerical models. In order to determine the optimum ranges for geometrical parameters of the elliptical cut, a parametric study was carried out using the verified FE models. Based on the results, the appropriate ranges for the cut parameters were recommended. Then, the cyclic behaviour of the connection with optimum parameters was compared with the conventional RBS and with different types of RWS connections. The results emphasised that the elliptical RWS connections according to the present recommendations provide appropriate cyclic performance in terms of ductility, rupture index, buckling stability, and ability to prevent the formation of plastic hinge near the column face. In addition, the flexural capacity of the proposed connection satisfied the requirements of the codes for special moment-resisting frames.